1993
DOI: 10.1017/s0025315400033051
|View full text |Cite
|
Sign up to set email alerts
|

Shell morphology and identification of early life history stages of congeneric species of Crassostrea and Ostrea

Abstract: Series of sequences of SEM micrographs are presented to elucidate species-specific shell features in larval and post-larval stages of four Ostreidae (Bivalvia) species (Crassostrea gigas (Thunberg), C. virginica (Gmelin), Ostrea edulis L., and O. equestris Say). The diagnostic characters, including hinge structure, shell shape, and the dimensions of the prodissoconch, are identified and summarized in a key at both generic and species levels. In larval Crassostrea the skewed, backwards-pointed umboned shells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 9 publications
3
22
0
Order By: Relevance
“…This reduction of the teeth in the posterior area, common in species of Crassostrea (Dinamani, 1976;Hu et al, 1993) was observed in this study, in C. rhizophorae larvae of 337 µm, in C. brasiliana of 390 µm and in C. gigas of 379 µm height. The anterior teeth of the left valve and of the right valve are present and vary in number among the studied species.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This reduction of the teeth in the posterior area, common in species of Crassostrea (Dinamani, 1976;Hu et al, 1993) was observed in this study, in C. rhizophorae larvae of 337 µm, in C. brasiliana of 390 µm and in C. gigas of 379 µm height. The anterior teeth of the left valve and of the right valve are present and vary in number among the studied species.…”
Section: Discussionsupporting
confidence: 82%
“…The variation observed in the length of the provinculum of the left valve, larger than the right valve, for the studied species is a consequence of the appearance of the distal teeth in the left valve. This increase in the length of the provinculum from this larval phase was also observed by Hu et al (1993).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…More frequently however, scanning electron microscopy (SEM) of larval hinge structures is being used to describe bivalve larvae. This is extremely useful in identifying closely related (congeneric) species with similar shell morphologies (e.g., Loosanoff et al 1966;Lutz & Hidu 1979;Hu et al 1993).…”
Section: Introductionmentioning
confidence: 99%